EIB Working Papers 2019/01 - Blockchain, FinTechs and their relevance for international financial institutions (Volume 2019/1) - Davradakis, Emmanouil; Santos, Ricardo; European Investment Bank; European Investment Bank (2019)
This paper provides an introduction to financial technology and blockchain, while exploring: the impact of FinTechs and TechFins on the financial sector, a description of blockchain technology and its applications, with a focus on cryptocurrencies, the impact on financial inclusion, risks and challenges, applications for international financial institutions and their clients.
Knowledge Unlatched
English
Keywords: Finance; Business & Economics; Finance; General